Identifications, Characteristics, and Expression Patterns of Small Heat Shock Protein Genes in a Major Mulberry Pest, Glyphodes pyloalis (Lepidoptera: Pyralidae). Issue 3 (4th May 2020) - Chu, Jie; Jiang, De-lei; Yan, Meng-wen; Li, Yi- jiangcheng; Wang, Jun; Wu, Fu-an; Sheng, Sheng
Abstract: Six candidate sHSP genes were identified from the Glyphodes pyloalis transcriptome. All sHSP genes included full-length open reading frames and shared high similarity with the sequences of other lepidopteran species. These sHSP genes encoded 175–191 amino acid residues, and the predicted proteins had a molecular weight from 19.5 to 21.8 kDa. All GpsHSPs were expressed at lower levels at larval stages. All GpsHSPs were expressed at higher levels at diapaused, prepupal, or pupal stages, suggesting that sHSPs may be involved in metamorphosis in G. pyloalis . In addition to the developmental stage, extreme temperatures can induce variations in the expression of sHSPs genes. All GpsHSPs were significantly upregulated in larvae following exposure to heat shock, except GpHSP21.4 which downregulated at 4 h following exposure to the cold shock treatment. Furthermore, Starvation influenced the expression patterns of GpsHSPs as a function of the duration of food deprivation. Four GpsHSPs increased their expression with time of starvation until reaching to the peak level at 6 d of starvation. Finally, parasitism by the endoparasitoid Aulacocentrum confusum He et van Achterberg (Hymenoptera: Braconidae)-induced fluctuations in the expression of all GpsHSPs, and the expression varied with time after parasitization. Our results from this study strongly suggest functional differentiation within the sHSPs subfamily in G. pyloalis . The present study would provide further insight into the roles of sHSPs in G. pyloalis and novel avenues for promoting integrated management of this pest.